The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0964528419828733
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral glucose metabolism after acupuncture at KI3 in spontaneously hypertensive rats: a positron emission tomography study

Abstract: Objective: The aim of this study was to explore the effect of acupuncture stimulation at KI3 on brain glucose metabolism in spontaneously hypertensive rats (SHRs). Methods: Brain glucose metabolism in SHRs after acupuncture stimulation at KI3 was detected using 18F-2-fluorodeoxy-D-glucose positron emission tomography (18F-FDG-PET). SHRs were randomly divided into three groups: no treatment (SHR group); acupuncture at KI3 (KI3 group); and sham acupuncture (Sham group). Wistar Kyoto (WKY) rats were used as a nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…49 Electroacupuncture at KI3 attenuates glucose metabolism in the hypothalamus and hypothalamus. 50 This might reduce sympathetic stimulation, which affects sleep status. For PMI patients, lower estradiol and higher luteinizing hormone levels are significantly involved.…”
mentioning
confidence: 99%
“…49 Electroacupuncture at KI3 attenuates glucose metabolism in the hypothalamus and hypothalamus. 50 This might reduce sympathetic stimulation, which affects sleep status. For PMI patients, lower estradiol and higher luteinizing hormone levels are significantly involved.…”
mentioning
confidence: 99%
“…As the high spatial but low temporal correlation [37], the neuroimaging techniques could not detect significant changes in the connectivity of these neural networks structures under certain circumstance [19]. Some researches demonstrated that the temporal dynamics of an ongoing Evidence-Based Complementary and Alternative Medicine "stream of consciousness" is much faster than the time resolution of blood oxygen lever-dependent (BOLD) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture treatment at the KI3 acupoint activated cerebral neurons and functional connectivity in elderly patients with mild cognitive impairment through functional magnetic resonance imaging (fMRI) [16,17]. In addition, KI3 stimulation regulated brain glucose metabolism in spontaneously hypertensive rats [18]. Furthermore, we demonstrated that EA treatment at KI3 acupoint regulated glucose metabolism in the transient vascular dementia animal model [19] and attenuated memory dysfunction by an increase of anti-neuroinflammation in the 5Xfamilial AD (FAD) model [20].…”
Section: Electroacupuncture (Ea) Is a Complementary Alternative Medicine Technique Widely Usedmentioning
confidence: 94%